AIAA Scitech 2021 Forum 2021
DOI: 10.2514/6.2021-0939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Engine Integration on a 4.6%-Scale Flying-V Subsonic Transport

Abstract: The installation and interference effects of an engine and nacelle to a 4.6%-scale half model of a Flying-V subsonic transport airplane are presented. Wind tunnel tests are performed at 20m/s in an open jet facility while balance measurements are taken to record lift, drag and pitching moment. The results show significant interference effects between the wing and engine. Interference drag is observed over the full range of angles of attack above 5 • , with a maximum of 60 drag counts (16.5% of isolated-wing dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The contribution of the engines to the forces and moments is quantified by using a model for the thrust coefficient, identified from the wind tunnel data of Ref. [9] using Ordinary Least Squares. The result is subtracted from the estimated forces and moments before the parameter estimation.…”
Section: G Engine Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of the engines to the forces and moments is quantified by using a model for the thrust coefficient, identified from the wind tunnel data of Ref. [9] using Ordinary Least Squares. The result is subtracted from the estimated forces and moments before the parameter estimation.…”
Section: G Engine Modelmentioning
confidence: 99%
“…The effect of engine integration on the aerodynamic interference was studied experimentally in Ref. [9]. It was shown that the interference effects on lift and pitching moment were of the same order of magnitude as the effect of superpositioning the contributions of the isolated wing and engine.…”
Section: Introductionmentioning
confidence: 99%